Condition assessment and Non-Destructive Testing on concrete structure at Pasar Awam Pagoh - Nik Abdul Majid, Nik Hafiz; Awang, Mariah; Abdul Rahman, Sr. Ts. Dr. Mohammad Ashraf (Progress in Engineering Application and Technology, 2022)
An existing concrete building will deteriorate over time due to a variety of factors, which will have an impact on the concrete’s durability and structural safety. As a result, assessing the current concrete quality of existing buildings is essential for ensuring safety. As a result, the goals of this study are to visually inspect the building and its surroundings, as well as to determine the concrete quality of the existing structure using the rebound hammer test (RHT) and the Ultrasonic Pulse Velocity Test (UPVT). Therefore, visual inspection was conducted at the beginning for achieves the first objective. Additionally, the rebound hammer test and Ultrasonic Pulse Velocity Test were conducted on ten selected columns and six selected columns for UPVT. The collected data was referenced with concrete quality. Based on the data collected from RHT test, it found that the highest quality of concrete is column 1 and the lowest concrete quality are column 8 and 9. Additionally, the result of UPVT test, it found that concrete quality was different with RHT which there are several Very poor concretes. From the result, the lowest concrete quality is column 1 and column 2. In conclusion, most of the concrete quality is considered as good layer although defects appeared.